2021
DOI: 10.2337/figshare.16712971.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduced Follicular Regulatory T Cells in Spleen and Pancreatic Lymph Nodes of Patients With Type 1 Diabetes

Abstract: In the attempt to understand the origin of autoantibody (AAb) production in patients with and at-risk for T1D, multiple studies have analyzed and reported alterations in follicular helper T cells (Tfh) in presymptomatic AAb-positive subjects and patients with T1D. Yet, it is still not clear whether the regulatory counterpart of Tfh cells, represented by follicular regulatory T cells (Tfr), is similarly altered. To address this question, we performed analyses in peripheral blood, spleen and pancreatic lymph nod… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Prior studies show that immune traits can be associated with specific genetic loci, including autoimmunityassociated single-nucleotide polymorphisms. These traits include immune subsets dysregulated in DS (such as decreased CXCR5 + B cells with Sjögren's syndrome-associated ds4938573 and increased T H 1 cells with PTPN22 C1858T) (73)(74)(75) and immune features associated with increased risk of autoimmunity in TCs (76,77). These findings support the notion that trisomy 21 alters immune architecture in ways that are associated with, and might drive, increased risk of autoimmunity.…”
Section: Discussionsupporting
confidence: 64%
“…Prior studies show that immune traits can be associated with specific genetic loci, including autoimmunityassociated single-nucleotide polymorphisms. These traits include immune subsets dysregulated in DS (such as decreased CXCR5 + B cells with Sjögren's syndrome-associated ds4938573 and increased T H 1 cells with PTPN22 C1858T) (73)(74)(75) and immune features associated with increased risk of autoimmunity in TCs (76,77). These findings support the notion that trisomy 21 alters immune architecture in ways that are associated with, and might drive, increased risk of autoimmunity.…”
Section: Discussionsupporting
confidence: 64%
“…Vecchione et al. have reported that the frequency of CXCR5 − FOXP3 + Tregs was higher in AAb + patients than in AAb − patients, which may be caused by active autoimmunity and metabolic dysfunction in AAb + patients 279 3), which were needed to maintain peripheral tolerance by regulating diabetogenic Tfhs and B cells, were reduced in spleen and pancreatic lymph node of patients with T1D.…”
Section: Treg Subsets In Autoimmune Diseasementioning
confidence: 99%
“…Treg subsets in type 1 diabetes T1D, a chronic autoimmune disorder, is characterized by insulin deficiency and resultant hyperglycaemia. [277][278][279] The complex interactions between the pancreatic β-cell and innate and adaptive immune systems lead to the progression of T1D. 280 In humans, Tfrs are identified that can inhibit the production of AAbs and restore glucose tolerance.…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…Blimp1 expression in Tfr was shown to be abundant in tumour tissue and associated with an increased risk of melanoma metastasis, suggesting that it may be a key mechanism for tumour cell immune evasion [22]. In clinical patients with type 1 diabetes, Tfr cells are reduced in the spleen and pancreatic lymph nodes, and restoration of Tfr cells by adoptive transfer in animal models slowed disease progression [23]. In addition, Tfr may regulate lymphangiogenesis and lipoprotein metabolism during atherogenesis by targeting Tfh and regulatory B cells [24].…”
Section: Therapeutically Targeting T Follicular Regulatory Cells In A...mentioning
confidence: 99%